2016
DOI: 10.1002/hep.28825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kinsenoside, a potential immunosuppressive drug for autoimmune hepatitis, on dendritic cells/CD8+T cells communication in mice

Abstract: The central purpose of this study was to investigate therapeutic effects of the botanical derivative, kinsenoside (KD), in experimental autoimmune hepatitis (AIH). Treatment with KD substantially reduced hepatic histopathological damage, induced by lymphocyte infiltration and proinflammatory cytokines, in concanavalin A-induced T-cell-mediated hepatitis, and in dendritic cells (DCs) loaded with hepatocellular carcinoma cells (DC/Hepa1-6) induced murine AIH. Interactions between immune cells after KD treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
0
36
0
3
Order By: Relevance
“…Cell suspensions were prepared from spleen, lymph nodes, VAT, or liver of ob/ob mice as previously described (Chang et al, 2015; Xiang et al, 2016). DC single-cell suspensions were obtained from bone marrow following standard procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell suspensions were prepared from spleen, lymph nodes, VAT, or liver of ob/ob mice as previously described (Chang et al, 2015; Xiang et al, 2016). DC single-cell suspensions were obtained from bone marrow following standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) was performed as described previously (Xiang et al, 2016). In brief, total RNA was isolated from cells, liver, or VAT using TRizol reagent, and reverse transcribed with the Revert Aid First strand cDNA synthesis kit (Invitrogen, USA) with random primers based on the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have found that kinsenoside had a different multiple pharmacologic activity compared with polysaccharide and flavonoids [5][6][7][8]. As a potential immunosuppressive drug for autoimmune hepatitis, it has a vascular protective effect under high glucose conditions and has been found to enhance the oxidative resistance of diabetic mice [9][10][11]. In addition, it has a reparative effect on damaged insulin cells and some other functions, such as anti-hyperliposis, anti-hyperglycemia, anti-osteoporosis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…When there is sufficient sterol, SREBP‐1 stays in the endoplasmic reticulum; however, when sterol is insufficient, SREBP‐1 is translocated to the Golgi, where it is cleaved and enters the nucleus to participate in the transcription of lipid synthesis‐related genes . In turn, SREBP‐1 expression can be directly regulated by the phosphatidylinositol 3‐kinase (PI3K) –protein kinase B ( AKT ) pathway, which plays a crucial role in glucose and lipid metabolism mediating interactions between the liver and immune cells . Therefore, activating the PI3K – AKT pathway can induce the expression and activation of SREBP‐1 by controlling its nuclear localization and thereby promoting its transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%
“…15 In turn, SREBP-1 expression can be directly regulated by the phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT) pathway, which plays a crucial role in glucose and lipid metabolism mediating interactions between the liver and immune cells. 16 Therefore, activating the PI3K-AKT pathway can induce the expression and activation of SREBP-1 by controlling its nuclear localization and thereby promoting its transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%